Experimentally and Numerical Investigation on Behavior of Annular RC Slabs under Ring Loading - Abdullah M. Abdal; Feirusha S. Hamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This research presents the experimentally measured displacement and strain at specified locations of the concrete of tested annular reinforced concrete slabs subjected to lateral load with three different ratios of inner to outer radii and simply supported at the outer circumference. Performed 3D model of annular RC slabs under the axisymmetric ring load applied, as close as at the inner edge, and investigated their stress-strain state in the elastic stage. This study contains different approaches based on classical thin-plate (CTP) theory and performed a 3D finite-element (FE) model to predict the fields of radial and circumferential stresses and deflection of the slab. Experimentally investigated the crack widths and crack pattern of the two groups of slabs-group A- radially reinforced and group M–orthogonally reinforced. added a correction factor to the CTP equations, which used to determine both radial and circumferential stresses. Also, investigated the appearance of the first cracks, deflection, failure mode, and the maximum value of the failure load for both cases of the reinforcement.